The medical insurance system's weakness to provide economic protection for vulnerable citizens in China: A five-year longitudinal study. (January 2021) - Wang, Nianshi; Gao, Wei; Ma, Meiyan; Shan, Linghan; Fu, Xuelian; Sun, Tao; Xia, Qi; Tian, Wanxin; Liu, Limin; Yang, Huiying; Shi, Baoguo; Li, Heng; et al.
Highlights: By comprehensive calculation on catastrophic health expenditure (CHE), it is precisely targeted the weakness of health insurance system for sufficient economic protection for Chinese middle-aged and elderly population in five years. It is identified the vulnerable characteristics of middle-aged and elderly population prone to CHE in China. Innovative use of the Generalized linear mixed models (GLMMs) is to find the fixed effect and random effect of the CHE in the five years. Abstract: Objectives: Little is known about the magnitude of catastrophic health expenditure (CHE) attributable to critical disease, especially in the middle-aged and elderly population. This research aimed to exploring the key aspects of how the health insurance fails to protect the middle-aged and elderly against CHE in the past five years. And propose corresponding measures to improve. Methods: Data were obtained from the 2011 to 2015 China Health and Retirement Longitudinal Study. The method was adapted from WHO to calculate the catastrophic health expenditure (CHE) and impoverishment by medical expense (IME), and use Generalized Linear Mixed Models (GLMMs) to comprehensively analyze the risk factors that cause middle-aged and elderly people to fall into CHE. Results: The incidence of CHE of China's middle-aged and elderly population has been rose in the five years from 2011 (10.5 %) to 2013 (17.5 %) to 2015 (19.7 %). The CHE of richest families was almost 6 times from 2011 to 2015. Urban Employee Medical Insurance Scheme, the incidence of CHE was up 10 percentage from 2011 to 2015. According to the GLMMs, families have inpatient cares as the most important factor to CHE. The incidence of CHE increased by 2.25 times compared with those who did not use inpatient services. Conclusions: The health system needs to control the irrational growth of health expenses and reduce residents' overuse of health services. Government should take supplementary measures to comprehensively strengthen the advantages of health insurance. Raise residents' awareness of health care, enhance citizens' physical fitness, and avoid unnecessary waste of health resources.